Modelling and simulation of dual active bridge converter and DC-AC converter in hardware-in-the- loop environment - Tong, Wen Yang (Nanyang Technological University, 2023)
The power grid is rapidly transforming into a complex cyber-physical system, where various distributed energy resources, microgrids, and smart inverters are key components. To keep up with this trend, new design and testing tools are essential. One such tool is the realtime Hardware-in-the-loop (HIL) simulation, which allows for comprehensive and reliable testing of power electronics systems. In this study, we focus on the modelling and simulation of a Dual Active Bridge Converter and DC-AC Converter using the Typhoon HIL simulation software. By conducting virtual simulations, we aim to consider all factors that can affect the performance of real circuits. Then, we compare the virtual simulation results with the real experimental data to assess the reliability of the experimental results. Our findings suggest that the proposed HIL simulation methodology can accurately simulate the Dual Active Bridge Converter and DC-AC Converter and provide valuable insights for control design and testing of power electronics systems. Overall, our study demonstrates the effectiveness of HIL simulation in ensuring the precision and reliability of power electronics experiments in the context of the evolving technological landscape.